Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2022
DOI: 10.1039/d1ay02040d
|View full text |Cite
|
Sign up to set email alerts
|

Rapid colorimetric discrimination of cyanide ions – mechanistic insights and applications

Abstract: In this work, we have employed an intramolecular charge transfer-based DMN colorimetric probe for the rapid naked-eye detection of cyanide ions in solution as well as real water samples. The...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 43 publications
(40 reference statements)
0
1
0
Order By: Relevance
“…It was previously reported that paper-based strips were appropriate for on-site detection applications. 58,59 In this regard, we have developed a CD-adsorbed paper-based analytical device for Fe 3+ detection. Whatmann filter paper was cut into small round strips and dipped in the aqueous CD solution.…”
Section: Development Of Paper-based Analytical Devicesmentioning
confidence: 99%
“…It was previously reported that paper-based strips were appropriate for on-site detection applications. 58,59 In this regard, we have developed a CD-adsorbed paper-based analytical device for Fe 3+ detection. Whatmann filter paper was cut into small round strips and dipped in the aqueous CD solution.…”
Section: Development Of Paper-based Analytical Devicesmentioning
confidence: 99%